(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article is devoted to journalistic activity, done by Agapiy Gonchaenko (1832-1916) – a Russian priest, publisher, journalist and public figure, one of the first political emigrants to the United States, deacon of the Russian embassy church in Athens, correspondent, typesetter of the Free Russian printing house in London – on the pages of the «Alaska Herald», issue organized and edited by himself, the first of the Russian press issues on the territory of America. His advanced editorials and comments were aimed at solving the most important socio-political and cultural problems of the Russian migrant in conditions abroad: the consequences of centuries of enslavement, paternalism and fatalism of a Russian person, disunity and the inability to rationally dispose of their own capabilities and resources. Keywords: Russian emigration, values, freedom, audience, Russian emigration, «Alaska Herald», Agapiy Gonchaenko. DOI 10.18522/1995-0640-2020-3-206-214